Study on the durability of conductive embroided yarns for application in interactive textiles - Dourado, Daniel (2016)
Interactive textiles based on electrically conductive yarns are being extensively research due to its ability to functionalize fibrous structures, leading to a high interactivity with the user. The aim of this study was to evaluate the durability of interactive embroidered 100% cotton fabrics, incorporating flexible conductive yarns composed of 77% polyamide (PA) and 23% silver (Ag) (30 tex) when subjected to wear factors such as washing, abrasion, creasing and stretching cyclic tests. The conductive yarns were incorporated on the fabric at two different widths of 2 to 10 mm, keeping a constant length of 10 cm. In order to study the durability of these materials, the fabrics were subjected to different washing cycles, according to the standard NP EN IS0 6330:2002, and to various abrasion cycles, according to the standard NPEN IS0 12947: 1999 showing an increased electrical resistance when testing time is increased. The increase on the electric resistance was more significant in the 2 mm width sample rather than the 10 mm sample. The recovery from creasing, measured according to standard NP EN 22313:1993, was further assessed and no significant changes were observed. It could be concluded that the durability of conductive embroidered textile substrates in terms of washing and abrasion is highly dependent on the width of the conductive yarns embroidered area to perform the function. Larger conductive embroidered areas were found to be significantly more stable to wear factors.